Tensile strength of wood in high temperatures before charring. (2nd March 2020) - Kuronen, Henri; Mikkola, Esko; Hostikka, Simo
Summary: The main focus of this paper is on the tensile strength of wood at high temperatures. On analysing previous literature, it was observed that results by different researchers are different, even though a vast reduction of the tensile strength at elevated temperatures was clear in all of them. Thus, a need for further investigation into the matter became apparent. As a key part of this paper, steady‐state tensile strength experiments below charring temperatures were carried out, and their results were analysed. The results were then used in analysing the tensile strength of a wooden beam subjected to a fire using the Fire Dynamics Simulator.